Why God-- why me? - Thomas, Peter, 1924-2016.; Hoffman, David; Hoffman, Jeanne; Schoeman, Sam.; Varied Directions, inc.; Knox County Child Abuse and Neglect Council; CustomFlix (Firm) ([S.l.] : CustomFlix, 2006)
The reality of child abuse/child sexual molestation is described by victims in Knox county.
Peter Thomas, narrator.
Producer, David Hoffman ; filmmakers, Jeanne Hoffman, Sam Schoeman.
"Knox County Child Abuse and Neglect Council."
Originally produced in 1988.
DVD.
Keywords: Child sexual abuse; Child abuse; Documentary films